Enhancing the phase distribution in parallel vertical channels with single and double chamber coaxial headers. (5th June 2019) - Marchitto, Annalisa; Fossa, Marco
Highlights: Experimental study of air-water phase distribution in parallel vertical channels. Comparison between a series of cylindrical distributors with in-line holes. Best distribution figure of merit for the "double chamber flute" fitting. A new overall performance parameter is used for data reduction. Abstract: In this paper, in order to maximize the degree of flow rate uniformity of the two phase flow distribution into parallel vertical channels, a number of distributor fittings have been tested with respect to a test section characterized by a horizontal header and a series of vertical upward channels. The fluids are air and water and the flow regimes at the header cover the intermittent and annular flow pattern conditions. The ranges of liquid and gas superficial velocities are 0.45–1.2 and 1.5–16.5 m/s, respectively. A header geometry without any inserts, such as the smooth reference header, is taken as a reference case. Data from a number of inserts to enhance the uniformity of distribution are compared to the reference case, such as a series of cylindrical distributors with in-line holes along their length ("flutes"). New data in particular are presented for the "double chamber flute" fitting. As in previous studies by the Authors, extracted mass flow rates of liquid and gas from parallel channels are recast in terms of normalized flow rates and normalized standard deviation of phases. A new overall performance parameter is used for data reduction and for summarizing the comparison between the flute fitting configurations.